The Moral Value in Iraqi Society between Change and Constant (Journal of the College of Education for Women, 2019)
The problem of constant and change values is one of the important problems that the philosophy thought had faced as the religious and social studies had taken it as it considers as one of the most dangerous which touch the basic . the research deals with the effect of change value of new Iraqi situation to be as an attempt , as participation or an excitement that can be occupied a space through the area of questions on the fix and change of moral values shed light on the economical ,social and political events that the Iraqi society passes through them .it is part of interests that becomes importance to everyone through the light of moral change Which is arbitrary to the life of the individual .It is not possible to rebuild the society or its people correctly unless it is preceded by moral reconstruction at all levels